Analisis Vegetasi Tingkat Pancang dan Anakan di Kawasan Taman Wisata Alam Pananjung Pangandaran - Aydin Rafif; Azfa Aulia; Salvia Calya Candra (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Pananjung Pangandaran Nature Tourism Park is one of the areas in Pangandaran Regency that is prioritized for tourism. As an area partially open to tourism activities, vegetation at the sapling and seedling levels in this TWA is vulnerable to disturbance. The existence of the plant species that make up the TWA area is inseparable from the needs of living things. Therefore, this study aims to determine the species composition and structure of vegetation at the sapling and seedling levels in Pananjung Pangandaran TWA. Data collection was conducted using a 240-m belt transect quadrat method in 12 plots. Data analysis included density, frequency, dominance, Importance Value Index (IVI), and Shannon-Wiener Diversity Index (H'). The study recorded 12 species from 8 families at the sapling level and 17 species from 13 families at the seedling level. The species with the highest IVI were the monkey-headed bulbul (Dysoxylum caulostachyum) at the sapling level (128.89%) and the bayur (Pterospermum javanicum) at the sapling level (115.55%). The Shannon-Wiener diversity index (H') values ​​at both levels were categorized as moderate (sapling = 1.88; sapling = 1.73). The results of this study are expected to provide scientific baseline data for managers in developing management strategies for the Pananjung Pangandaran Nature Tourism Park area. Keywords: Saplings, Vegetation Analysis, Diversity, Saplings, Pangandaran Nature Tourism Park Abstrak Taman Wisata Alam Pananjung Pangandaran merupakan salah satu kawasan di Kabupaten Pangandaran yang diunggulkan dalam sektor pariwisata. Sebagai kawasan yang sebagian arealnya terbuka bagi kegiatan wisata, vegetasi pada tingkat pancang dan anakan di TWA ini rentan terhadap gangguan. Keberadaan jenis-jenis tumbuhan penyusun kawasan TWA tidak akan pernah lepas dari kebutuhan makhluk hidup. Oleh karena itu, penelitian ini bertujuan untuk mengetahui komposisi jenis serta struktur vegetasi tingkat pancang dan anakan di TWA Pananjung Pangandaran. Pengumpulan data dilakukan dengan metode kuadrat belt transect sepanjang 240 m pada 12 plot, sedangkan analisis data meliputi kerapatan, frekuensi, dominansi, Indeks Nilai Penting (INP), dan Indeks Keanekaragaman Shannon-Wiener (H'). Hasil penelitian mencatat 12 spesies dari 8 famili pada tingkat pancang dan 17 spesies dari 13 famili pada tingkat anakan. Spesies dengan INP tertinggi adalah pisitan monyet (Dysoxylum caulostachyum) pada tingkat pancang (128,89%) dan bayur (Pterospermum javanicum) pada tingkat anakan (115,55%). Nilai indeks keanekaragaman Shannon-Wiener (H’) pada kedua tingkat termasuk kategori sedang (pancang = 1,88; anakan = 1,73). Hasil penelitian ini diharapkan menjadi data dasar ilmiah bagi pengelola dalam menyusun strategi pengelolaan kawasan TWA Pananjung Pangandaran. Kata kunci: Anakan, Analisis Vegetasi, Keanekaragaman, Pancang, Taman Wisata Alam Pangandaran